The concept of conversation : from Cicero's Sermo to the Grand Siècle's conversation - Randall, David, 1972- (Edinburgh University Press, 2018)
In the classical period, conversation referred to real conversations, conducted in the leisure time of noble men, and concerned with indefinite philosophical topics. Christianity inflected conversation with universal aspirations during the medieval centuries and the ars dictaminis, the art of letter writing, increased the importance of this written analogue of conversation. The Renaissance humanists from Petrarch onward further transformed conversation, and its genre analogues of dialogue and letter, by transforming it into a metaphor of increasing scope. This expanded realm of humanist conversation bifurcated in Renaissance and early modern Europe. The Concept of Conversation traces the way the rise of conversation spread out from the history of rhetoric to include the histories of friendship, the court and the salon, the Republic of Letters, periodical press and women. It revises Jürgen Habermas' history of the emergence of the rational speech of the public sphere as the history of the emergence of rational conversation and puts the emergence of women's speech at the centre of the intellectual history of early modern Europe -- Provided by the publisher.